The Drosophila homolog of methionine sulfoxide reductase A extends lifespan and increases nuclear localization of FOXO. - Chung, H.; Kim, A.K.; Jung, S.A.; Kim, S.W.; Yu, K.; Lee, J.H. (FEBS Letters, 2010)
Methionine sulfoxide reductase A (msrA) was previously found to increase resistance to oxidative stress and longevity in animals. We identified Drosophila msrA (dmsrA), a Drosophila homolog of human msrA, as a downstream effector of forkhead box O (FOXO) signaling in Drosophila, which enhances resistance to oxidative stress and increases survival under stressed conditions. Additionally, overexpression of dmsrA in neurons extended the lifespan of flies. Moreover, overexpression of dmsrA in fat body cells caused FOXO to translocate to the nucleus, implying that this possible positive feedback loop between dmsrA and FOXO could potentiate the antioxidant activity of dmsrA and increase the lifespan in Drosophila.